2014
DOI: 10.1111/zsc.12048
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic analysis of Pseudopaludicola (Anura) providing evidence of progressive chromosome reduction

Abstract: Here, we present a molecular phylogenetic analysis of the Neotropical genus Pseudopaludicola focusing on species relationships including 11 of the 17 known species of Pseudopaludicola; several samples of Pseudopaludicola are not assigned to any species; and 34 terminal species as an outgroup. The study was based on the analysis of approximately 2.3 kb of the sequence of the mitochondrial 12S rRNA, tRNAval and 16S rRNA genes through maximum parsimony and Bayesian phylogenetic reconstruction approaches. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 47 publications
6
56
0
7
Order By: Relevance
“…(2) Pseudopaludicola sp. 2 (Serra do Cipó) and P. giarettai were not included in the cladogram of Veiga‐Menoncello et al (), although they were included here due to having 2 n = 18 chromosomes and tail morphology equal to that of the other members of this clade. Axoneme (ax), axial fiber (af), juxta‐axonemal fiber (jf), paraxonemal rod (pr), undulating membrane (um).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Pseudopaludicola sp. 2 (Serra do Cipó) and P. giarettai were not included in the cladogram of Veiga‐Menoncello et al (), although they were included here due to having 2 n = 18 chromosomes and tail morphology equal to that of the other members of this clade. Axoneme (ax), axial fiber (af), juxta‐axonemal fiber (jf), paraxonemal rod (pr), undulating membrane (um).…”
Section: Resultsmentioning
confidence: 99%
“…These authors confirmed the considerable variation in diploid chromosome numbers originally observed by Beçak () and Batistic (), confirming the existence of four distinct groups, with 2 n = 16, 2 n = 18, 2 n = 20, and 2 n = 22. The molecular phylogeny of Veiga‐Menoncello et al () identified four clades that were consistent with these four chromosomal groups. This study also confirmed the monophyly of the genus Pseudopaludicola and the paraphyly of the species with simple phalanges in comparison with the pusilla group.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Lynch (1989) proposed the Pseudopaludicola pusilla (Ruthven, 1916) species group for P. boliviana Parker, 1927, P. ceratophyes Rivero & Serna, 1985, P. llanera Lynch, 1989, and P. pusilla, which share the morphological feature of T-shaped terminal phalanges. In subsequent analyses, Lobo (1995) and Veiga-Menoncello et al (2014) corroborated the monophyly of the P. pusilla group.…”
mentioning
confidence: 78%
“…Pseudopaludicola is recognized as monophyletic based on external morphological (Lynch 1989;Lobo 1995), such as the presence of a hypertrophied antebrachial tubercle, osteological (Lobo 1995), and molecular evidence (Veiga-Menoncello et al 2014). Lynch (1989) proposed the Pseudopaludicola pusilla (Ruthven, 1916) species group for P. boliviana Parker, 1927, P. ceratophyes Rivero & Serna, 1985, P. llanera Lynch, 1989, and P. pusilla, which share the morphological feature of T-shaped terminal phalanges.…”
mentioning
confidence: 99%